L’enquête des Volontaires de Tianjin. Un objet social complexe au prisme de la sociologie et des humanités numériques - Aurélia Desplain; Isabelle Thireau (Humanités Numériques)
This article presents the use of the various digital tools offered by the Oronce Fine platform to contextualise and reconstruct the inquiry carried out by the Volunteers of Tianjin (China), a collective inquiry aimed at identifying the historical, architectural or political value of the city’s buildings suddenly threatened with destruction. The use of a geographic information system, first of all, has made it possible to collect and preserve old maps in a durable manner, to georeference, annotate and develop linked metadata layers. In addition, the digital exhibition of photographs and postcards has contributed to the access and preservation of rich data for the social sciences. Finally, the publication of multimedia narratives aims to allow users of the site to explore the complexity and innovation of the Volunteers’ inquiry.